Effect of Production of Soybean Milk Mixed with (Perilla frutescens) Phuangsavat PHIMSALA and Vonesy LOKHAMHEUANG - PHIMSALA , Phuangsavat; LOKHAMHEUANG, Vonesy (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
The objective of this experiment was to study the consumer acceptance with the 9-point hedonic scale on the production of soybean milk mixed with (Perilla frutescens) and storage age by store in the refrigerator and room temperature (20 days), Conduct laboratory research in food science and technology, Faculty of Agriculture and Forest Resources Souphanouvong University The experimental design was RCBD (Randomized Completely Block Designed), with 3 replications and 3 treatments. Experiment with this temperature at 100 ° C for 1 hour, by boiling in a vacuum, use a different ratio of sesame juice, aroma and taste with Pandanus juice and sugar at 3 levels (3 experimental things) as T1 (1:0:0:0); T2 (1:0.2:0.1:0.1) and T3 (1:0.3:0.1:0.1) respectively. Results found that the pH values ​​tend to decrease as: T1, T2 and T3 are equal to 6.39; 6.05 and 5.86 respectively, on the contrary to the Brix values, there is an upward trend is 8.5; 12 and 15 respectively and there was a statistically significant difference at the 95% confidence level (p≤ 0.05). When mixing soy milk products with sesame juice that goes through the convert processing, set at the refrigerator and room temperature for 24 hours, from the visual observation, the color scheme did not change on all 3 trials: white, light gray and dark yellow respectively, percentage stability at the refrigerator and room temperature It was found that T1 was significantly higher than T2 and T3 with values of 99%, 98%, 90% and 95%, 95%, 81%, respectively and statistically significant at 95% confidence level (p≤ 0.05). Consumer sensory test results it was found that T2 received the highest recognition scores in terms of features as color, brightness, overall, Sweet, aroma of sesame mix Pandanus, flavor of beans, overall taste, feeling after swallow and Overall preferences the values are 7.76, 7.14, 7.74, 7.74, 7.56, 7.48, 7.52, 7.48 and 7.88 respectively, overall, all three tests were statistically significant at the 95% confidence level (P≤0.05) (except for brightness and flavor of beans). From the 20-day at refrigeration storage age assessment found that total microbes equal to 28.4x 10 CFU/ml, Compared to the community standard, the soy milk community (529/2004. Thailand) is still safe to consume. Therefore, considering the physical and sensation quality analysis, it is possible to conclude that T2 is best suited liquid character, light gray, do not separate layers, scent of beans and sesame, fragrance Pandanus mixed with beans and sesame, the average sweetness score is in line with the 12˚Brix sweetness and consumers are also interested in buying up to 96% and the potential for future sales.